HUBUNGAN PENGETAHUAN TENTANG VAKSIN (MAESLES RUBELLA) DAN PENDIDIKAN IBU DENGAN MINAT KEIKUTSERTAAN VAKSIN DI PALEMBANG - lina contesa (IKesT Muhammadiyah Palembang, 2022)
Introduction: Measles and rubella are infectious diseases transmitted through the respiratory tract. Rubella is a mild disease in children, but it can cause adverse effects, if it occurs in pregnant women in the first trimester, namely miscarriage or disability in babies, it is often called Congenital Rubella Syndrome. Methods: The design of this study was analytical observational with a cross sectional research design. The research instrument used a check list and interview. The population in this study were mothers of children aged 5 years totaling 65 respondents and the sampling technique used was accedental sampling. The analysis used univariate and bivariate with Chi-Square test. Results: Based on univariate analysis, the results of high knowledge and interest were 89.2% and mother's education level was 87.7%. The results of the Chi-Square statistical test showed that there was a relationship between knowledge about MR Vaccine and interest in participating in MR Vaccination (p value 0.001 < 0.05). Conclusion: There is a relationship between mother's knowledge about the MR vaccine and the interest in participating in the MR (Maesles Rubella) vaccination at the integrated clinic and growth and development at the Palembang Bari Hospital, Children with the MR vaccine (Maesles Rubella) and those who are not vaccinated against MR (Maesles Rubella) more at risk of adverse effects on children's health.